The application of cluster mapping technique in writing descriptive paragraphs - Rahayu (International Journal in Applied Linguistics of Parahikma, 2020)
The objective of this study was to examine the effect of using cluster mapping technique to the writing ability of the second-year students of state junior high school (SMPN) 4 Makassar. A quasi-experimental design was adopted in this study. The population of this research was the second year students of SMPN 4 Makassar in the academic year 2018/2019. The researcher used cluster random sampling technique to determine the two classes involved as sample. Class VIII.5 consisting of 36 students was assigned as experimental group and class VIII.6 composed of also 36 students was involved as control group. There were two variables in this research, namely the use of cluster mapping technique as independent variable and students’ writing ability as dependent variable. The data were collected from writing tests administered in pretest and posttest of each group. The posttest results demonstrated that the experimental class was significantly better than control class. The posttest mean score of experimental class (70.86) was higher than the control group (65.86), and the value of t-test was higher than the value of t-table (5.144>1.994). Based on the findings and discussion of the study, it can be concluded that the cluster mapping technique can significantly improve the ability in writing descriptive paragraph of the second-year students of SMPN 4 Makassar.